If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 = f + (-30) 3 = f + -30 Reorder the terms: 3 = -30 + f Solving 3 = -30 + f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-1f' to each side of the equation. 3 + -1f = -30 + f + -1f Combine like terms: f + -1f = 0 3 + -1f = -30 + 0 3 + -1f = -30 Add '-3' to each side of the equation. 3 + -3 + -1f = -30 + -3 Combine like terms: 3 + -3 = 0 0 + -1f = -30 + -3 -1f = -30 + -3 Combine like terms: -30 + -3 = -33 -1f = -33 Divide each side by '-1'. f = 33 Simplifying f = 33
| -2(-3)+10= | | (6x^5+4)*(6x^5-4)= | | 5(18)-7= | | 9x+23=48 | | (-7/x-2)+(3-2x/x) | | 30G^3C^2=0 | | 2a+4=15 | | (5a+6)*(5a-6)= | | 5u+63x*4h=9 | | 3(2x+3)=2(3+x) | | -(7-4x)=0 | | 1-6x=19-9x | | 3x=(-1) | | 5x-7(x-9)=29 | | -6x+2=2(5-x) | | 0.5(3t+2)-0.25(x+6)= | | 15/-4 | | 3x+x-9=3 | | -1/4+y=-3/5 | | 0,7x=2,8 | | 7+2y=4 | | 0.57x-0.08=-0.10x+5.28 | | -2(2x+3)=5-4x | | 36+12x=42+8x | | 1/2x6x6x3 | | (x-3/4x+4)(x^2-x-2/x+2) | | 0.5(3t+2)-0.25(tz+6)= | | 2(x-1)=7x+4 | | x(5x-2)*(x+3)= | | 3.3q-4.6-4.9q=-4.6 | | 4a-6b= | | -8=-(5/x-8) |